2021
DOI: 10.1002/tcr.202100214
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Boronic Ester Architectures: Synthesis, Host‐Guest Chemistry, Dynamic Behavior, and Supramolecular Catalysis

Abstract: Dedicated to Professor Koichi Narasaka with Gratitude on the Occasion of his 77 th Birthday (Kiju).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Multi-component self-assembly typically gives highly symmetric structures, as widely observed in nature. 11–16 This principle for the high symmetry lies behind the large entropy loss in the self-assembly process, simply due to the drastic decrease in the number of molecules in the system. However, the entropy loss is relatively compensated when the molecular components are located at equivalent environments in the self-assembly, leading to information loss (entropy increase) of the components in the system.…”
Section: Confined Spaces In Resorcin[4]arene Assemblies Directed By H...mentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-component self-assembly typically gives highly symmetric structures, as widely observed in nature. 11–16 This principle for the high symmetry lies behind the large entropy loss in the self-assembly process, simply due to the drastic decrease in the number of molecules in the system. However, the entropy loss is relatively compensated when the molecular components are located at equivalent environments in the self-assembly, leading to information loss (entropy increase) of the components in the system.…”
Section: Confined Spaces In Resorcin[4]arene Assemblies Directed By H...mentioning
confidence: 99%
“…11–14 Dynamic covalent chemistry also produces covalent cage structures with internal cavities from binary or ternary molecular components. 15,16 Similar to the natural system, multiple hydrogen bonds can provide unique molecular assemblies under thermodynamic control. 17 Thanks to the dynamic nature of the reversible hydrogen bond formation, the careful design of molecular units can extend cage frameworks to create large internal spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, they utilized a crown-ether-based macrocycle 62 to promote the Diels–Alder reaction (Table 6). 46,69 Due to the presence of crown ether rings, macrocycle 62 could capture K + , which is essential to accelerate the Diels–Alder reaction. It was reported that the reaction rate is accelerated up to 206-fold compared to catalyst-free systems.…”
Section: Applications Of Boron-containing Macrocyclesmentioning
confidence: 99%
“…By contrast, the connecting five-membered ring in boronate esters derived from catechols and boronic acids constitutes a highly linear and planar conjunction predestined for directional self-assembly (Figure a, bottom). In recent years, the unique boronate ester motif has been implemented in a growing number of highly versatile structures and complex 3D architectures . Selected examples include fluorinated cages or a giant [8 + 12] cage with an additional exoskeleton constructed via postsynthetic alkene metathesis from the Mastalerz group.…”
Section: Introductionmentioning
confidence: 99%